Damages caused by hurricane Irma in the human-degraded mangroves of Saint Martin (Caribbean) - Walcker, R. (Sci Rep, 2019)
In early September 2017, Irma was the most powerful hurricane that struck the northern Caribbean over the last 100 years. In the 21(st) century, the stronger types of tropical cyclones will likely increase in frequency due to the climate change and internal climate variability. Lessons to anticipate the response of mangroves to this intensification can be learned from this extreme event. Here, we analysed damages caused in mangrove forests of the Saint Martin Island. Mangroves of this island were previously degraded due to historic human pressures and recent over-urbanisation. Forest inventories and time series of very high resolution satellite images revealed that approximately 80% of the mangrove area was damaged by the hurricane. Results highlighted distinct rates of forest recovery. Early and rapid recoveries were largely observed in most study sites. However, some mangroves were still unable to recover fourteen months after the disturbance. The human-induced degradation of the ecosystem prior to the hurricane is hypothesised to be the main factor controlling the absence of forest recovery. We suggest that human-degraded mangroves will be weakened in the face of such extreme events. We advocate to preserve and restore mangroves in order to guarantee all the valuable ecosystem services they provided.